1974
DOI: 10.1037/h0036998
|View full text |Cite
|
Sign up to set email alerts
|

Temporal control, attention, and memory.

Abstract: Animals do not usually respond for food at times when it is not available, such as the time just after food delivery on periodic schedules. Consequently, food acquires inhibitory aftereffects (inhibitory temporal control) on such schedules so that its omission elevates subsequent response rate (omission effect). Data and arguments are presented to show that temporal control depends on the properties of memory and attention. Maintained reinforcement-omission effects reflect temporal overshadowing of neutral eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
74
0
7

Year Published

1976
1976
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 55 publications
6
74
0
7
Order By: Relevance
“…Thus, our results cannot be explained by the internal pacemaker account per se, but they do suggest that there are contributions from some other processes, such as the memory or decision components in temporal processing. This agrees with recent theories that hypothesize that a working memory forms the basis of temporal perception (Lewis & Miall, 2006;Matell & Meck, 2004;Niki & Watanabe, 1979;Staddon, 1974;Staddon & Higa, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…Thus, our results cannot be explained by the internal pacemaker account per se, but they do suggest that there are contributions from some other processes, such as the memory or decision components in temporal processing. This agrees with recent theories that hypothesize that a working memory forms the basis of temporal perception (Lewis & Miall, 2006;Matell & Meck, 2004;Niki & Watanabe, 1979;Staddon, 1974;Staddon & Higa, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…This provides direct support for the hypothesis that an animal's response to reinforcement omission is determined by a stimulus complex that minimally includes the omission event and component cues. As Staddon (1974) posits, a presumably neutral stimulus (in this case a time-out) is inherently less salient to a hungry animal than is a food reinforcement, an assumption that has since found empirical support (Spetch & Wilkie, 1981). However, the neutral stimulus can interact with other stimuli, in this case a change of key color, to signal the initiation of a new schedule component.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of reinforcement, the subject may fail to discriminate this transition; short delays and second-component stimuli similar to the first component facilitate this lack of discrimination, that is, they make the transition more difficult to perceive. Staddon (1974) has used similar logic to argue against the "Wagner control" (Wagner, 1959) procedure which provided results commonly cited as evidence against the possibility that reinforcement inhibits responding. Wagner found that rats that were never reinforced in the first goalbox of a double runway ran more slowly to the second goalbox than did experimental rats that had experienced reinforcement omission in the first goalbox following a history of continuous reinforcement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations